2016
DOI: 10.1103/physrevlett.117.217401
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controlled Bistability of a Dark Soliton Train in a Polariton Fluid

Abstract: We use a one-dimensional polariton fluid in a semiconductor microcavity to explore the rich nonlinear dynamics of counter-propagating interacting Bose fluids. The intrinsically driven-dissipative nature of the polariton fluid allows to use resonant pumping to impose a phase twist across the fluid. When the polariton-polariton interaction energy becomes comparable to the kinetic energy, linear interference fringes transform into a train of solitons. A novel type of bistable behavior controlled by the phase twis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…This reduced drag has been explained by the finite lifetime of Bogoliubov modes due to drain present in this open system [30]. In addition it has been realised that elementary excitations known from equilibrium condensates exist too-dark solitons are feasible in 1d [32,33] or quantised vortices in 2d non-equilibrium condensates [34,35] above a specific critical velocity or even spontaneously due to purely non-equilibrium dynamics [36]. The mathematical extension of the governing partial differential equation for open BEC in those scenarios implies intrinsic adaptions of the excitations' mathematical form [32,37] (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This reduced drag has been explained by the finite lifetime of Bogoliubov modes due to drain present in this open system [30]. In addition it has been realised that elementary excitations known from equilibrium condensates exist too-dark solitons are feasible in 1d [32,33] or quantised vortices in 2d non-equilibrium condensates [34,35] above a specific critical velocity or even spontaneously due to purely non-equilibrium dynamics [36]. The mathematical extension of the governing partial differential equation for open BEC in those scenarios implies intrinsic adaptions of the excitations' mathematical form [32,37] (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of GPE makes it possible to describe fundamental properties of dark and bright solitons in a polariton condensate, such as their dynamics, stability, and continous emission [27][28][29][30][31][32][33][34]. Successful creation of nonlinear excitations and their manipulation gave rise to a new concept of information processing based on vortices and soliton dynamics [35][36][37]. It is important to note that using dark solitons or quantized vortices for information processing devices requires a precise description of nonlinear dynamics, which is the aim of our work.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polaritonic systems are easily controllable by optical techniques and, due to their finite lifetimes, are ideal systems for studying outof-equilibrium phenomena [8,9]. In analogy with the atomic case [10,11], condensation [12] and the superfluid behavior of polaritonic quantum fluids [13] have been of great theoretical interest [14-16] and have been experimentally confirmed [17][18][19].Recently, multi-pumps settings were explored to form polariton condensates by off-resonant excitation of spatially distinct areas [20,21], and to study the collision of strongly interacting fluids in a resonant excitation regime [22][23][24]. This allows for example the condensa-tion of polaritons in a pump-free zone surrounded by the excitation spots [20] or the formation of nonlinear collective excitations (dark solitons and vortices) with resonant driving [22][23][24].…”
mentioning
confidence: 99%
“…In analogy with the atomic case [10,11], condensation [12] and the superfluid behavior of polaritonic quantum fluids [13] have been of great theoretical interest [14-16] and have been experimentally confirmed [17][18][19].Recently, multi-pumps settings were explored to form polariton condensates by off-resonant excitation of spatially distinct areas [20,21], and to study the collision of strongly interacting fluids in a resonant excitation regime [22][23][24]. This allows for example the condensa-tion of polaritons in a pump-free zone surrounded by the excitation spots [20] or the formation of nonlinear collective excitations (dark solitons and vortices) with resonant driving [22][23][24]. Interestingly, it is found that the density of such excitations diminishes as the interactions increase [24] and that the strong interactions regime can lead to the merging of vortex-antivortex (V-AV) pairs [25], paving the way to a perfect merging of distinct Bose gases, as reported here.In the present work, we focus on achieving the complete vanishing of all interference and the annihilation of all phase singularities inside a two-dimensional, square geometry four-pumps system.…”
mentioning
confidence: 99%